Analisis penerapan media interaktif terhadap peningkatan minat dan motivasi belajar yang baik untuk siswa mi miftahul jannah - Agustini, Afifah; Yaqin, Firdaus Ainul; Amalia, Nur Fitri (Universitas Sebelas Maret, 2025)
Media plays an important role in the classroom because it can foster students, curiosity, motivate them, and touch their souls. The use of learning media at the teaching orientation stage improves the learning process and the delivery of materials in a simple and easy way. The research method uses a qualitative approach. The purpose of the study was to increase students` low interest and motivation in learning, the results of the study showed that the application of interactive media is very useful and has many positive impacts on students so that it can foster interest and motivation in students.